Analysis of Consumer Perceptions Based on Service Quality at Umi Syifa Canteen and Sipadipulut Canteen MSMEs - Zaharah, Raja Putri; Astari, Yanisha Dwi (Pinisi Business Administration Review, 2026)
This study aims to analyze consumer perceptions based on service quality at Umi Syifa Canteen and Sipadipulut Canteen during the Polbeng Business Expo Chapter II. A quantitative research approach with a descriptive and explanatory design was employed. Data were collected from consumers who made purchases at both MSMEs using an accidental sampling technique. The research instrument was a structured questionnaire measuring service quality dimensions, including responsiveness, reliability, assurance, empathy, and tangibles. The data were tested for validity and reliability and analyzed using classical assumption tests and simple linear regression analysis. The results indicate that service quality has a positive and significant effect on consumer perceptions, indicating that higher service quality leads to more favorable consumer evaluations. These findings show that consumer perceptions are strongly shaped by direct service interactions during the purchasing process. Therefore, improving service quality is essential for culinary micro, small, and medium enterprises to enhance positive consumer perceptions, customer satisfaction, and business sustainability.